Multifunctional T cell response in convalescent patients two years after ZIKV infection. Issue 4 (29th July 2020) - Pereira Neto, Tertuliano Alves; Gonçalves‐Pereira, Marcela Helena; de Queiroz, Camila Pereira; Ramos, Michele Faria; de Oliveira, Fernanda de Fátima Souza; Oliveira‐Prado, Roberta; do Nascimento, Valdinete Alves; Abdalla, Ligia Fernandes; Santos, João Hugo Abdalla; Martins‐Filho, Olindo Assis; Naveca, Felipe Gomes; Teixeira‐Carvalho, Andrea; et al.
Abstract: Zika is an important emerging infectious disease in which the role of T cells remains elusive. This study aimed to evaluate the phenotype of multifunctional T cells in individuals 2 yr after exposure to Zika virus (ZIKV). We used a library of 671 synthetic peptides covering the whole polyprotein of ZIKV in pools corresponding to each viral protein (i.e., capsid, membrane precursor or prM, envelope, NS1 [nonstructural protein], NS2A + NS2B, NS3, NS4A + NS4B, and NS5) to stimulate PBMCs from individuals previously exposed to ZIKV. We observed an increased frequency of ZIKV‐specific IFNγ, IL‐17A, TNF, and IL‐10 production by T cell populations. IFNγ and TNF production were especially stimulated by prM, capsid, or NS1 in CD8+ T cells and by capsid or prM in CD4+ T cells. In addition, there was an increase in the frequency of IL‐10+ CD8+ T cells after stimulation with prM, capsid, NS1, NS3, or NS5. Multifunctional properties were observed in ZIKV‐specific T cells responding especially to prM, capsid, NS1 or, to a smaller extent, NS3 antigens. For example, we found a consistent IFNγ + TNF+ CD8+ T cell population in response to most virus antigens and CD4+ and CD8+ T cells that were IFNγ + IL‐17A+ and IL‐17A+IL‐10+, which could also produce TNF, in response to capsid, prM, NS1, or NS3 stimulation. Interestingly, CD8+ T cells were more prone to a multifunctional phenotype than CD4+ T cells, and multifunctional T cells were more efficient at producing cytokines than single‐function cells. This work provides relevant insights into the quality of ZIKV‐specific T cell responses and ZIKV immunity. Graphical Abstract: ZIKV induces type 1 and type 17 immune responses with multifunctional signatures combining IFNγ, TNF, and IL‐17A production by CD4+ and CD8+ T cells